The tactics of ship collision avoidance based on Quantum‐behaved Wolf Pack Algorithm. (20th February 2019) - Liu, Hongdan; Sun, Rong; Liu, Qi
Summary: To ensure the navigational safety of ships in the sea and reduce human errors, a set of navigational information systems with decision support function is developed. Fast and stable collision avoidance actions are also adopted according to the ship risk level and encounter situation. Therefore, the ship automation collision avoidance tactics based on Quantum‐behaved Wolf Pack Algorithm (QWPA) is proposed complied to COLREG in this paper, and then feasibility and effectiveness of which have been positively verified in laboratory conditions based on the three‐degree‐of‐freedom ship mathematical model; compared with existing collision avoidance scheme, the quality and generating speed of the collision avoidance strategy are enhanced greatly under different ship encounter situation.